Pengaruh Penganggaran, Budget Empahasis, Asimetri Informasi Pada Budgetary Slack Dengan Locus Of Control Sebagai Pemoderasi - Dwi Riantari, Kadek Ayu Mika; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
This study aims to determine the effect of budgeting, budget emphasis and information asymmetry on budgetary slack and to find out locus of control as moderating participatory budgeting, budget emphasis and information asymmetry on BPR budgetary slack in Tabanan Regency. This research was carried out by rural banks spread across Tabanan Regency. The population were budget compilers in 22 BPRs. The technique of determining the sample purposive sampling with criteria of selected informants who had occupied the position / part of at least 2 years and contributed to the preparation of the budget. Data collection by distributing questionnaire. Data analysis technique used is MRA. The results indicate that budgetary, empahasis budget, information asyimmetry has a positive effect on budgetary slack. Locus of control moderates the influence of participatory budgeting, budget empahasis and information asymmetry on budgetary slack. Keywords : Budgeting; Budget Empahasis; Information Asymmetry; Budgetary Slack; Locus Of Control.